How Does Entrepreneurial Competence Contribute to Livestock Farmers’ Performance? - Mikael Sihite; Eka Nur Jannah; Alex Johanes Simamora; Wildan Yudhanto (Binus Business Review, 2025)
The research aimed to examine (1) the direct effect of entrepreneurial skill, market orientation, sales orientation, and networking on entrepreneurial competence; (2) the direct effect of entrepreneurial competence on livestock farmers’ performance; and (3) the indirect effect of entrepreneurial skill, market orientation, sales orientation, and networking on livestock farmers’ performance through entrepreneurial competence. Samples were 399 livestock farmers in Magelang Regency. The independent variables were entrepreneurial skills, market orientation, sales orientation, and networking. Meanwhile, the dependent variable was livestock farmers’ performance, and the mediating variable was entrepreneurial competence. Variable measurement used 7-Likert scale questionaries. Then, data analysis used Structural Equation Modeling (SEM). Based on data analysis, the research finds that entrepreneurial skill, market orientation, sales orientation, and networking improve entrepreneurial competence. In addition, entrepreneurial competence increases livestock farmers’ performance, Then, entrepreneurial skill, market orientation, sales orientation, and networking improve livestock farmers’ performance through entrepreneurial competence. The research contributes to giving new evidence of entrepreneurial competence in the context of animal husbandry. The research also contributes to capturing how the implementation of the Resources-Based View (RBV) concept affects the achievement of livestock farmers’ performance. The research has some implications. First, livestock farmers increase entrepreneurial competence by building entrepreneurial skills, market orientation, sales orientation, and networking to improve performance. Second, regulators can formulate regulations or programs that can help livestock farmers to grow their businesses since the business is run individually, such as human resource development or business establishment programs.